Zur Wiedergabe deutscher erweiterter Attribute in authentischen norwegischen Übersetzungen - Solfjeld, Kaare (HERMES - Journal of Language and Communication in Business, 2004)
In Norwegian non-ﬁctional prose expanded prenominal attributes are less frequently used than in German non-ﬁctional prose. This article looks into the different strategies used by professional translators when expanded attributes are translated into Norwegian. Authorized translations show a variety of different target structures, including a strong tendency to produce analogous target structures, but at the same time a clear tendency to delete explicit lexical material in the translation process. The ﬁndings suggest a ‘trade-off’ between ‘expanding’ strategies with a high degree of explicitness on a superordinate level and ‘reduction’ strategies with a tendency to implicitness on subordinate levels.